No influence of prematch subjective wellness ratings on external load during elite Australian football match play - Bellinger, P. N.; Ferguson, C.; Newans, T.; Minahan, C. L. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To determine whether there is an association between external match load and contextual factors on subjective wellness in the days before and after Australian Rules football match play. Methods: A total of 34 elite male Australian football players completed a subjective wellness questionnaire in the days leading into the match (-3, -2, and -1 d), the day of (match day), and the days after each match (+3, +2, and +1 d). Players subjectively rated each item (mood, energy, stress, leg heaviness, muscle soreness, sleep quality, hours slept, and total wellness [a sum of the total response score]) on a visual analog scale ranging from 1 to 10, with 1 representing the negative end of the continuum. External load during competitive matches was quantified using accelerometer-derived PlayerLoad, and running activity was quantified using global positioning system technology across 2 competitive seasons. The relationships between perceptions of wellness (within-individual z score), external match load, and contextual factors (match result, match location, and between-matches recovery duration) were analyzed using linear mixed models. Results: Mixed-effect linear models revealed trivial effects of match-day wellness z score on subsequent external match load metrics. Match result (win) and PlayerLoad in the anteroposterior vector (au·min-1) were associated with an increased (estimate?±?SE: 0.30?±?0.13 z score) and reduced subjective wellness (-0.15?±?0.06 z score), respectively. Conclusion: The results of this study suggest that prematch perceived wellness does not relate to external match load in elite Australian football players. The between-matches microcycle length appears to be sufficient to restore perceived wellness to values that do not affect the subsequent external match loads.